STUDI TAKSONOMI PEMBUATAN BELIUNG PRASEJARAH DI NGRIJANG SENGON, NGRIJANGAN, GUNUNG GAMPING, KENDENG LEMBU : APLIKASI ANALISIS KLUSTER STEINHAUS DAN UJI D/MA - Yusuf Ernawan (BRIN, 2001)
The relationship between the stone reduction stages and the presence of physical defects can show the product and debitage according to the purpose of stone adze making. The relationship between the physical defects and the sequence of stages of stone reduction to proto-adze and adze shows that each group always does not have completely flaked products, so it does not show products that are suitable for the purpose of forming proto-adzes.